New steroidal saponins with l-arabinose moiety from the rhizomes of Smilax scobinicaulis. (September 2017) - Shu, Jicheng; Zhu, Genhua; Huang, Guangyu; Huang, Huilian; Liang, Yonghong; Liu, Xing; Yu, Jiangli; Zhou, Meng; Li, Linyu; Deng, Jiao
Graphical abstract: Highlights: Four new steroidal saponins withl -arabinose moiety were isolated from Smilax scobinicaulis . The structures of new compounds were determined on the basis of 1D and 2D NMR spectroscopy. Compounds 3 and 4 exhibited significant inhibition on HCT-116 and SGC-7901 cells. Abstract: Phytochemical investigations of the rhizomes of Smilax scobinicaulis led to the isolation of seven steroidal saponins (1 –7 ) of which four (1, 3, 4 and6), nameed, Smilscobinosides C-F, respectively) are new. Five of these steroidal saponins withl -arabinose moiety are reported here for the first time in the genus Smilax . The structures were elucidated by spectroscopic analysis of the isolates and their hydrolysis products. The isolated compounds were evaluated for their cytotoxicity against four human tumor cell lines (SH-SY5Y, SGC-7901, HCT-116 and Lovo). Compounds3 and4 exhibited significant inhibition on HCT-116 (with IC50 values of 10.5 and 7.8 μM) together with inhibition on SGC-7901 (with IC50 values of 21.4 and 15.8 μM), respectively.